Revolutionizing Text Data Analysis with AI Autocoding with NVivo - Lumivero (Lumivero, 2023)
As the original AI qualitative data analysis software, NVivo has fine-tuned the autocoding feature that lets researchers conduct text data analysis with AI to detect and code themes and sentiments.
KerkoCite.ItemAlsoKnownAs: 2129771:EEGIN4JK 2405685:UNJD6IY6 2486141:PA4EZZ36